The technology, chemistry, and microbiology of Serra Cheese: a review - Macedo, Angela C. (2011)
This paper comprehensively reviews fundamental and applied aspects of the manufacture of Serra cheese, its composition, the biochemical reactions that take place during coagulation and ripening, and the microbial ecology. Serra cheese is the most traditional cheese manufactured in Portugal. Aspects that make it unique are 1) its manufacture by the coagulation of raw ewe milk using a vegetable rennet (cardoon flower) and 2) its final buttery texture and flavor. The wide variation of the final quality of this “Appelation d’Origine Controllée” cheese has been explained by the intrinsic variabilities of raw materials, cheese-making practices, and maturation. The available studies pertaining to Serra cheese have indicated that 1) the coagulant activity of cardoon flower extract on ewe milk is higher and is more affected by pH and salt concentration than that of animal rennet, 2) the best coagulation temperature is 27 to 29°C, 3) the best ripening conditions are 8°C and 90% relative humidity, 4) the lactic acid fermentation results mainly from the action of lactic acid-type Streptococcus, Leuconostoc, and Lactobacillus species, 5) a yellow to reddish surface viscous material (mainly composed of yeasts) is important in the ripening process, 6) maturation is essentially surface-driven, and 7) the low temperatures prevailing during winter help to control the extensive microbial contamination that occurs from the poor sanitary conditions during cheese manufacture. These points are described and critically discussed in light of the principles of dairy science.